Occupational relevance of subclavian vein thrombosis in association with thoracic outlet syndrome - Fiorentini, Cristiana; Mattioli, Stefano; Graziosi, Francesca; Bonfiglioli, Roberta; Armstrong, Tom J.; Violante, Francesco S. (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'Primary subclavian vein thrombosis (“effort thrombosis”) is not generally recognized as a work-related disorder, and more knowledge is required on the particular biomechanical risks. An extensive biomechanical risk analysis was performed for a possible work-related case. Case report A hard-working 43-year-old race-course farrier received successful surgical treatment for subclavian vein thrombosis. No congenital abnormalities were apparent. At work, the farrier spent 75% of his time with his back bent (generally at >70 degrees) with his right shoulder flexed and abducted, a position that thereby increased the pressure on the subclavian vein. High average (and peak) stress ratings for the neck and shoulder postures are accompanied by high levels of force and considerable repetitiveness. ' ' CONCLUSIONS ': 'Taken together, these forms of biomechanical overload suggest that the leading cause of the subclavian thrombosis suffered by this farrier could have been occupational. Case–control studies on this neglected topic are needed to investigate possible associations between subclavian vein thrombosis and specific occupational activities.
Keywords: biomechanical assessment; biomechanics; case report; effort thrombosis; occupational disease; occupational relevance; subclavian vein thrombosis; thoracic outlet syndrome; work-related disease